The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1530/eje-22-0074
|View full text |Cite
|
Sign up to set email alerts
|

Primary hyperaldosteronism induces congruent alterations of sodium homeostasis in different skeletal muscles: a 23Na-MRI study

Abstract: Background: Sodium homeostasis is disrupted in many cardiovascular diseases, which makes non-invasive sodium storage assessment desirable. In this regard, sodium MRI has shown its potential to reveal differences in sodium content between healthy and diseased tissues as well as treatment-related changes of sodium content. When different tissues are affected disparately, simultaneous assessment of these compartments is expected to provide better information about sodium distribution, reduce examination time, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…These results consolidate the notion that cardiac function deterioration induced by excessive aldosterone is largely dependent on salt status. Recently, Christa et al found that PA patients showed treatment-reversible significantly higher tissue sodium signals in the myocardium, calf muscle, and skin compared to healthy controls ( Christa et al, 2019 ; Christa et al, 2022 ). This is a novel explanation for the relationship between sodium and LV hypertrophy in PA. BNP is a neurohormone that is activated by volume expansion and pressure overload of cardiac ventricles ( Epshteyn et al, 2003 ), In the present study, our results show that TASK −/− mice exhibit obvious sodium retention and a rise in BNP and β-MHC mRNA levels in LV tissue.…”
Section: Discussionmentioning
confidence: 99%
“…These results consolidate the notion that cardiac function deterioration induced by excessive aldosterone is largely dependent on salt status. Recently, Christa et al found that PA patients showed treatment-reversible significantly higher tissue sodium signals in the myocardium, calf muscle, and skin compared to healthy controls ( Christa et al, 2019 ; Christa et al, 2022 ). This is a novel explanation for the relationship between sodium and LV hypertrophy in PA. BNP is a neurohormone that is activated by volume expansion and pressure overload of cardiac ventricles ( Epshteyn et al, 2003 ), In the present study, our results show that TASK −/− mice exhibit obvious sodium retention and a rise in BNP and β-MHC mRNA levels in LV tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies mainly led by Titze’s group have shown that tissue sodium reservoir expands and contracts depending on the salt intake ( 9 ). Increased muscle and skin sodium concentrations have furthermore been observed in patients with refractory hypertension, primary aldosteronism, heart failure and insulin resistance ( 11 , 12 , 14 , 15 , 17 ), most of which are associated with increased activity of GC and MC ( 18 , 19 , 20 ).…”
Section: Discussionmentioning
confidence: 99%
“…Since 23 Na is a nucleus with a fast multi-exponential signal decay a relevant part of the signal could not be detected with the sequence used due to the echo time of 2.01 ms. Consequently, we do not report absolute values of tissue sodium but the relative sodium signal intensity (rSSI) which is the 23 Na signal intensity of the calf muscle relative to a reference vial containing an aqueous solution with a concentration of 100 mmol/L that was scanned with every participant. This concentration was chosen to avoid bias during calibration, as it provided a signal-to-noise ratio high enough for calibration (11,15) while even higher concentrations might have induced image artifacts outside the vial.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The hormones secreted by adrenal gland play an important role in the metabolism ( Sevilla et al, 2013 ), regulation of blood pressure ( Reincke et al, 2021 ), and homeostasis of sodium or glucose ( Kuo et al, 2015 ; Christa et al, 2022 ). Natural products may influence secretion of hormones from adrenal gland.…”
Section: Effect Of Natural Products On Hormones Secreted By the Adren...mentioning
confidence: 99%